Characteristics of structural changes of the retina in early period of traumatic optic nerve damage in the experiment - Leskiv, Halyna; Moyseyenko, Nataliya (ScienceRise: Medical Science, 2024)
The aim of this study was to characterize the structural changes of the retina in the early period of traumatic damage to the optic nerve. Materials and methods. The research used a model of crushing the optic nerve. The study was conducted on 30 mature rabbits with a body weight of 2.0 kg to 2.5 kg. Morphological examinations included light and electron microscopy. The retina of the right eye (control) and left eye (lesion side) was evaluated on the 14th day of the experiment. The animals were kept and removed from the experiment (through an overdose of narcotic drugs – ketamine) in accordance with the "Bioethical Requirements of the Helsinki Declaration on the Ethical Regulation of Medical Research". Protocol No. 125/22 dated March 24, 2022. The results. The results of the morphological study showed structural changes occurring in the retina on the 14th day after traumatic damage to the optic nerve, namely the presence of microcirculation disorders and the development of edematous and destructive processes. Neurons exhibit degenerative changes such as karyopyknosis, vacuolization, and colliquative necrosis. Lipofuscin inclusions were recorded in the layer of nerve fibers. On the other hand, presumably restorative and compensatory processes are observed, such as the appearance of young mitochondria and endoplasmic reticulum hypertrophy and hyperplasia. The thickness of the layer of ganglion cells of the retina increased by 52 %, and the nerve fibers layer – by 35 % on the affected side compared to the control side. What is found may be the result of the damage itself, but at the same time it can be seen as a protective mechanism and contribute to future recovery. Conclusions. It was found that changes in cytoarchitectonics of the retina in the early period of traumatic damage to the optic nerve are manifested by a combination of degenerative and restorative processes